Keefektifan Social Media Marketing Platform Instagram Pada Usaha Bisnis Gadadua Dalam Menembus Pasar Internasional - Rambitan, Reita Andrian (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the effectiveness of the Instagram social media marketing platform as a strategic tool in facilitating Gadadua's business ventures to enter international markets. By utilizing a social media marketing framework, this research analyzes the extent to which Gadadua's presence on Instagram can influence recognition, customer interaction, and sales conversions in international markets. This research method includes qualitative data analysis in the form of interviews with related parties and the three layers of social media method which includes data collection from social media statistics. The research results show that Instagram is effective as a marketing platform for Gadadua, with an increase in the number of followers, interactions and sales. The practical implications of this research include recommendations for improving social media marketing strategies, use of creative content, and customer engagement to maximize Instagram's potential as an effective marketing tool in a global market context.